The Influence Of Communication, Confidence And Appearance On Service User Satisfaction At The Bangkalan Tax Service Office - Radityo Angga Primantoko; Sri Rahayu; Rifda Fitrianty (International Publisher (YAPENBI), 2023)
This study examines the influence between communication, confidence and appearance on service user satisfaction at the Bangkalan Tax Service Office. The population of this study were all taxpayers registered at KPP Pratama Bangkalan, totaling 86,815 taxpayers. The sampling technique is because the population is known, a cross-sectional sample is used, based on the sampling technique the researcher decides to take 96 respondents to be studied. The results showed that simultaneously the variables of communication, confidence and appearance had an effect on service user satisfaction at the Bangkalan Tax Service Office, while partially the variables of communication, confidence and appearance had a significant effect on service user satisfaction at the Bangkalan Tax Service Office.